The influence of parenteral protein intake on electrolyte disturbances in premature infants - Carlos Javier Parramón-Teixidó; Laura Gómez-Ganda; Beatriz Garcia-Palop; Marcos Linés-Palazón; Albert Blanco-Grau; Jose Bruno Montoro-Ronsano; Susana Clemente-Bautista (Elsevier, 2021)
Introduction: Aggressive parenteral nutrition with delivery of high amino acid and energy doses is used to improve growth and neurodevelopmental outcomes in very low birth weight (VLBW) preterm infants. Recent findings, however, suggest that this approach may cause electrolyte imbalances. The aim of our study was to compare the prevalence of hypercalcaemia, hypophosphataemia, and hypokalaemia in 2 groups of preterm infants that received parenteral nutrition with different amounts of amino acids and to analyse perinatal and nutritional variables associated with the development of electrolyte imbalances. Methods: We conducted a retrospective observational study comparing 2 groups of preterm infants born before 33 weeks' gestation with birth weights of less than 1500 g managed with parenteral nutrition. One of the groups received less than 3 g/kg/day of amino acids and the other received 3 g/kg//day of amino acids or more. We analysed the prevalence of electrolyte imbalances and possible associations with aggressive parenteral nutrition, adjusting for potential confounders. Results: We studied 114 infants: 60 given less than 3 g/kg/day of amino acids (low-intake group) and 54 given at least 3 g/kg/day (high-intake group). The prevalence of electrolyte imbalances was similar in both groups. The prevalence of hypercalcaemia was 1.67% in the low-intake group and 1.85% in the high-intake group (P > .99), the prevalence of severe hypophosphataemia 11.7% vs 9.3%, and the prevalence of hypokalaemia 15.0% vs 11.1% (P > .99). A calcium to phosphorus ratio greater than 1.05 had a protective effect against hypophosphataemia (P = .007). Conclusions: We did not find an association between hypercalcaemia, hypophosphataemia, and hypokalaemia and the amino acid dose delivered by PN in the high-intake group of preterm infants. Resumen: Introducción: La nutrición parenteral agresiva con aportes energéticos y proteicos altos se utiliza para mejorar el crecimiento y el neurodesarrollo en recién nacidos prematuros de muy bajo peso. No obstante, hallazgos recientes sugieren que su uso puede ocasionar alteraciones electrolíticas. El objetivo del estudio era comparar la prevalencia de hipercalcemia, hipofosfatemia e hipopotasemia en dos grupos de recién nacidos prematuros que recibieron nutrición parenteral con distintos aportes de aminoácidos, y analizar variables perinatales y nutricionales asociadas a la ocurrencia de alteraciones electrolíticas. Métodos: Estudio retrospectivo observacional, con comparación de 2 grupos de recién nacidos prematuros con peso < 1500 g y edad gestacional < 33 semanas manejados con nutrición parenteral. Uno de los grupos recibió < 3 g/kg/d de aminoácidos mientras que el otro recibió ≥3 g/kg/d. Se analizó la prevalencia de distintas alteraciones electrolíticas y su asociación con la nutrición parenteral agresiva, con ajustes para posibles factores de confusión. Resultados: El análisis incluyó 114 recién nacidos: 60 que recibieron < 3 g/kg/d de aminoácidos (ingesta baja) y 54 que recibieron ≥ 3 g/kg/d (ingesta alta). La prevalencia de alteraciones electrolíticas fue similar en ambos grupos. La prevalencia de hipercalcemia fue de 1,67% en el grupo de ingesta baja y 1,85% en el grupo de ingesta alta (p >  0,99). Los respectivos valores para las otras alteraciones fueron 11,7% vs. 9,3% en el caso de la hipofosfatemia grave y 15,0% vs. 11,1% en el caso de la hipopotasemia (p >  0,99). Se observó que una relación calcio:fósforo superior a 1,05 ofrecía un efecto protector frente a la hipofosfatemia (p = 0,007). Conclusiones: No se observó asociación entre la hipercalcemia, hipofosfatemia o la hipopotasemia y el aporte de aminoácidos mediante nutrición parenteral en la población de recién nacidos prematuros con ingestas altas de aminoácidos.